Anti-Inflammatory, Antioxidant and Antibacterial Properties of Tomato Skin and Pomegranate Peel Extracts: A Sustainable Approach for Oral Health Care - Alessia Silla; Angela Punzo; Francesca Bonvicini; Matteo Perillo; Marco Malaguti; Antonello Lorenzini; Ismaela Foltran; Dario Mercatante; Mara Mandrioli; Maria Teresa Rodriguez-Estrada; Silvana Hrelia; Cristiana Caliceti (Antioxidants)
Agricultural food waste and by-products could provide high-value compounds that positively affect human and environmental health, thus representing promising ingredients for cosmeceutical products. This study explores the biological activities of tomato skin (HP) and pomegranate peel (PPE) extracts on oral mucosa to evaluate their possible use in mouthwashes. The biological activities of the extracts and the mouthwash (MW) containing them were evaluated in Human Primary Gingival Epithelial cells (HGECs). The antioxidant and anti-inflammatory activities were analyzed in HGECs injured with lipopolysaccharides. After 24 h of treatment with PPE, HP, and MW, significant antioxidant activity and an increased Superoxide Dismutase 1 expression (p < 0.01) were observed. Additionally, the extracts significantly reduced the expression of tumor necrosis factor α (p < 0.05) and Monocyte Chemoattractant Protein 1 (p < 0.001), suggesting an anti-inflammatory role. Lastly, the antibacterial activity was assessed against Streptococcus mutans and Streptococcus sanguinis by the broth microdilution method and agar cup diffusion test for the extracts and the mouthwash, respectively, demonstrating strong effectiveness against both oral streptococcus species. Results demonstrate the potential of HP and PPE in reducing oxidative stress, inflammation, and bacterial proliferation within oral mucosa, highlighting food waste up-cycling as a resource for human health.